On‐Site, On‐Demand 3D‐Printed Nasopharyngeal Swabs to Improve the Access of Coronavirus Disease‐19 Testing. Issue 11 (21st August 2021) - Song, Jiaxi; Korunes‐Miller, Jeremy; Banerji, Rohin; Wu, Yuanqiao; Fazeli, Shoreh; Zheng, Hanqiao; Orr, Beverley; Morgan, Elise; Andry, Christopher; Henderson, Joel; Miller, Nancy S.; White, Alice; et al.
Abstract: Diagnostic testing that facilitates containment, surveillance, and treatment of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), or future respiratory viruses, depends on a sample collection device that efficiently collects nasopharyngeal tissue and that can be manufactured on site when an outbreak or public health emergency is declared by a government. Here two novel stereolithography‐based three‐dimensional (3D)‐printed nasopharyngeal swabs are reported which are made using a biocompatible and sterilizable photoresist. Such swabs are readily manufactured on‐site and on‐demand to ensure availability, if supply chain shortages emerge. Additionally, the 3D‐printed swabs easily adapt to current workflow and testing procedures in hospital clinical laboratories to allow for effortless scaling up of test kits. Finally, the 3D‐printed nasopharyngeal swabs demonstrate concordant SARS‐CoV‐2 testing results between the 3D‐printed swabs and the COPAN commercial swabs, and enable detection of SARS‐CoV‐2 in clinical samples obtained from autopsies. Abstract : This article presents two novel stereolithography‐based 3D‐printed nasopharyngeal swabs fabricated using a biocompatible and sterilizable resin that are readily manufactured on‐site and on‐demand. Mechanical and clinical evaluations demonstrate non‐inferior performance of 3D‐printed swabs to commercial swabs. These versatile designs are transferable to many other swab types such as, oropharyngeal and anterior nasal swabs.